Carcinoma Avançado do Colo do Útero: Tratamento Inicial pela Quimioterapia - Andrade, Jurandyr Moreira de (2023)
A new approach to the treatment of advanced cervical carcinoma was utilized in order to make patients operable. Forty patients in stages lla, llb and II Ib ofthe disease were initially treated with chemotherapy (cisplatinum 80-100/m2/cycle and bleomycin 15 mg/cycle) followed by radiotherapy. After combined treatment, 21 patients could be operated upon (12 Wertheim Meigs and nine pan-hysterectomies), without further complications. 85.7% of the operated tumors were exophytic, andonly 19.3% endophiticus. No residual tumors were foundin eight patients (21.7%> ofthe cases). Samples obtained by pelvic lymphadenectomy revealed a low percentage of nodular metastasis (16.7%). Two patients who died and one who had a recurrence on the vaginal fornix were from the endophytic group. We conclude that combined chemotherapy and radiotherapy were effective in rendering more than half the patients susceptible to surgery. Exophytic tumors had the best prognosis in terms of clinical response and disease-free survival. Chemotherapy probably reduced the percentage of pelvic node metastasis.